Bullying dalam al-Qur’an dan Relevansinya dengan Kehidupan Modern - Hadi, Rifki; al-Munawwar, Said Agil Husin; Huda, Ade Naelul (STAINI Press, 2025)
In the modern era like today, there are still many cases of oppression, both verbally and physically, perpetrated by individuals or groups. This act is known as bullying. This writing analyzes the expressions of verses related to bullying, whether in the form of verbal, physical, or social bullying in the Qur'an. This article is examined qualitatively using a thematic approach. The primary data sources used in this research are contemporary interpretation books with a sociocultural emphasis, namely the Tafsir al-Munîr by Wahbah az-Zuhaylî, Tafsir Al-Azhar by Buya Hamka, and Tafsir Al-Mishbah by Quraish Shihab. The research results show that from 11 verses of the Qur'an related to bullying, there are at least three (3) types of bullying, namely verbal, physical, and social. The commentators explain that bullying includes mocking, spreading false news, giving bad nicknames, and exposing someone's shame or secrets. Although the model of bullying in this era has evolved into cyberbullying, these actions remain a form of criminal behavior as harmful as traditional bullying in the real world.